2004
DOI: 10.1021/ja039093l
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of an Enzymatic Substitution Reaction in Haloalkane Dehalogenase

Abstract: Reactive flux molecular dynamics simulations have been carried out using a combined QM/MM potential to study the dynamics of the nucleophilic substitution reaction of dichloroethane by a carboxylate group in haloalkane dehalogenase and in water. We found that protein dynamics accelerates the reaction rate by a factor of 2 over the uncatalyzed reaction. Compared to the thermodynamic effect in barrier reduction, protein dynamic contribution is relatively small. However, analyses of the friction kernel reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
130
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(142 citation statements)
references
References 84 publications
(231 reference statements)
10
130
2
Order By: Relevance
“…Nam et al studied the recrossing events both in DHase and in water with activated dynamics calculations based on a QM/MM potential energy surface. 169 The recrossing transmission coefficients they obtained are 0.53 and 0.26 in enzyme and in water, respectively. They demonstrated that the reaction rate is enhanced in the enzyme by reducing the dynamical recrossing by a factor of 2 compared to the uncatalyzed reaction in water; hence, dynamical recrossing contributes to the enzyme catalysis, although it is not the most dominant factor.…”
Section: Haloalkane Dehalogenasementioning
confidence: 92%
“…Nam et al studied the recrossing events both in DHase and in water with activated dynamics calculations based on a QM/MM potential energy surface. 169 The recrossing transmission coefficients they obtained are 0.53 and 0.26 in enzyme and in water, respectively. They demonstrated that the reaction rate is enhanced in the enzyme by reducing the dynamical recrossing by a factor of 2 compared to the uncatalyzed reaction in water; hence, dynamical recrossing contributes to the enzyme catalysis, although it is not the most dominant factor.…”
Section: Haloalkane Dehalogenasementioning
confidence: 92%
“…Simulation studies of many enzymatic processes have addressed and also raised many important issues in enzyme catalysis such as covalent catalytic mechanisms [28,29], contribution of the preorganized electrostatic environment of enzymes [30,31], the effects of strain and conformational dynamics of the enzyme-substrate complex, non-equilibrium dynamical effects, and quantum tunnel ling effects [32,33].…”
Section: Modeling Enzyme Catalysismentioning
confidence: 99%
“…For a multidimensional condensed-phase system such as the active site of an enzymecatalyzed reaction, it is not always clear how best to choose the reaction coordinate. Most work uses a simple function of valence coordinates (e.g., geometrical parameters such as a dihedral angle or the difference between the making and breaking bond lengths), 11,13,36,55,[167][168][169][170] whereas other studies employ a collective bath coordinate, as in Marcus theory: 29,32,68-70,73,171,172,183 (12) where V R and V P are, respectively, the energy of the diabatic reactant electronic state and the diabatic product electronic state. 60,68 In many cases, it is possible that both definitions of the reaction coordinate are adequate.…”
Section: Reaction Coordinatesmentioning
confidence: 99%
“…116 All molecular dynamics simulations were performed using periodic boundary conditions for a system consisting of 29 540 atoms, of which 15 atoms from DCE and Asp124 are treated quantum mechanically. 169 The energy barrier for the gas-phase reaction is 21.3 kcal/mol from the ion-dipole complex to the transition state using the AM1-SRP model, corrected to the best theoretical result at the G2 level of theory. 217 The PMFs were determined along the mass-weighted asymmetric stretch coordinate involving the nucleophile, the substrate, and the leaving group, and the free energies of activation were found to be 26.7 and 15.8 kcal/mol for uncatalyzed and enzymecatalyzed reaction, respectively, 169,217 in good accord with the corresponding experimental values of 28.2 (this is an extrapolated barrier from higher temperature measurements as typically done for slow spontaneous reactions 2,5 ) and ~15.3 kcal/mol.…”
Section: Desolvation and Reactant State Effectsmentioning
confidence: 99%